2018
DOI: 10.1021/acs.jproteome.7b00683
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Fate of 13C-Labeled Polydextrose and Impact on the Gut Microbiome: A Triple-Phase Study in a Colon Simulator

Abstract: The present study introduces a novel triple-phase (liquids, solids, and gases) approach, which employed uniformly labeled [U-C] polydextrose (PDX) for the selective profiling of metabolites generated from dietary fiber fermentation in an in vitro colon simulator using human fecal inocula. Employing C NMR spectroscopy, [U-C] PDX metabolism was observed from colonic digest samples. The major C-labeled metabolites generated were acetate, butyrate, propionate, and valerate. In addition to these short-chain fatty a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 67 publications
4
13
0
Order By: Relevance
“…Moreover, also Erysipelotrichaceae has been shown to be stimulated by fibre intake (e.g. Lamichhane et al, 2018), and in this study with 13 C-labelled polydextrose was correlated with increased SCFA production.…”
Section: Please Cite This Article As 'In Press'supporting
confidence: 61%
See 1 more Smart Citation
“…Moreover, also Erysipelotrichaceae has been shown to be stimulated by fibre intake (e.g. Lamichhane et al, 2018), and in this study with 13 C-labelled polydextrose was correlated with increased SCFA production.…”
Section: Please Cite This Article As 'In Press'supporting
confidence: 61%
“…However, as mentioned above we cannot exclude that the metabolism of certain taxa changed (from acetate/propionate to butyrate), without major shifts in composition. Future studies with 13 C-labelled substrates, similar to the ones done by us and others before, might shed a light on that (Binsl et al, 2010;de Graaf et al, 2010;Lamichhane et al, 2018).…”
Section: Please Cite This Article As 'In Press'supporting
confidence: 55%
“…The fraction of the bacterial subclass Erysipelotrichaceae; Other has been shown to increase following the consumption of β-glucans and inulin [ 34 ]. These bacteria participate in the production of short-chain fatty acids [ 35 ]. In the present study, the fraction of Erysipelotrichaceae; Other was increased by the consumption of vegetables rich in soluble dietary fiber, which also caused an actual increase in short-chain fatty acid concentrations.…”
Section: Discussionmentioning
confidence: 99%
“…A study using 13 C-labeled PDX showed that the major 13 C-labeled metabolites in colon simulator samples were acetate, butyrate, propionate, and valerate. In addition, minor amounts of 13 C-labeled lactate, formate, and succinate were detected 14 . Another in vitro human colon simulator study using PDX 15 showed higher levels of acetate, butyrate, propionate, and succinate, and lower levels of certain amino acids, valerate, formate, isovalerate, and trimethylamine in PDX samples compared to control samples.…”
Section: Introductionmentioning
confidence: 99%